Behold!!! The Protong — Potop i Małpoludy, czyli teodycea Stanisława Szukalskiego - Teske, Joanna Klara (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2012)
The essay is devoted to the original theory of Zermatism developed by Stanisław Szukalski between 1940 and 1987, and presented to the public in fragments in the album Behold!!! The Protong (1980). Though intended as a work of science, the theory may be interpreted as a work of art, whose leading theme is theodicy: an attempt to defend God’s goodness (and, additionally, man’s nobility) in the face of evil. In Szukalski’s theory, suffering either is a side-effect of Interplanetary Laws, against which God (the Sun) is powerless, or results from hostile actions of ugly Manapes, whose malice against beautiful mankind reflects their sorrowful alienation. Suffering, therefore, does not imply either God’s indifference or human wickedness. Szukalski’s insistence that his work should be taken as scientific rather than artistic might indicate the artist’s desire for his vision to be true.